Production of bio-ethanol from biomass waste (sugarcane) - Mohd Hisyam, Yusop (2006)
The purposes of this study are to produce ethanol from waste sugarcane using pre-treatment with alkali pre-treatment, enzymatic hydrolysis and anaerobic fermentation. The studies will focus on optimize various alkali pre-treatment condition with respect to final ethanol yield using sugarcane bagasse as feedstock. Different pre-treatment parameters (time and concentration) will be evaluated with intention of finding conditions which generate high sugar yields. In this experiment there are three stages to be completed in order to produce ethanol. In first stage, the sample will be through sodium hydroxide pre-treatment with certain temperature and time. At the second stage, the sample will be exposed to enzymatic hydrolyzes by a blend of Cellulast 1.5L and Novozym 188 cellulase mixture. Finally process fermentation with Saccaromyces cerevisae will be done in anaerobic condition. At the end of the research, the sample pre-treated with sodium hydroxide at 2% concentration for 2 hour gives the higher concentration of glucose and ethanol which obtained 16.58 mg/ml and 14.59 by volume %.